FEELING RESPONSIBLE AND INTEGRATED: A CHALLENGE TO INTELLECTUALISM ABOUT AGENCY - Ribeiro, Leonardo de Mello (Princípios: Revista de Filosofia (UFRN), 2015)
Reflection is put at the forefront of rational agency (in the sense of acting for a reason) by what we will call here ‘the intellectualist tradition’. According to this tradition, there is a sort of qualitative distinction between actions which are the result of reflection and those which are simply motivated by pro-attitudes like desires. One long-standing problem with such qualitative distinction is concerned with the so many swift, quasi-automatic actions we perform in everyday life. How can these be accommodated within the intellectualist framework? In the context of these actions and of providing an answer to that question, our aim here is to highlight another problem with that qualitative distinction: one which is related to our natural feelings of responsibility for our actions. In the end, we shall suggest that only an account of rational agency that holds an “internal”, straightforward relation between desires and actions would be able to make sense of those feelings.